Informative value of neurophysiological and neuroimaging research methods in the onset of spinal cord myelopathy: literature review and clinical observation - D. S. Kanshina; M. A. Surma; E. V. Badamshina; O. Yu. Bronov (Нервно-мышечные болезни)
Vascular myelopathy is a variant of acute or subacute lesions of the spinal cord as a result of circulatory disorders in the local vascular basin or hemodynamic changes in the vessels of distant localization.A clinical case of a patient with vascular myelopathy at the thoracic level is presented, the anamnesis of the disease, the results of examination and instrumental research methods with an assessment of the significance of diagnostic transcranial magnetic stimulation at the onset of the disease are presented.The purpose of this publication is to demonstrate the informative value of diagnostic transcranial magnetic stimulation and magnetic resonance imaging in the onset of vascular myelopathy of the spinal cord.A clinical case of a patient with vascular myelopathy at the thoracic level is presented, the history of the disease, the results of examination and instrumental methods of investigation are considered, with an assessment of the significance of diagnostic transcranial magnetic stimulation in the onset of the disease. A review of the literature was carried out in order to assess the information content of neurophysiological and neuroimaging studies in vascular myelopathy. In patients with onset of spinal cord infarction, the study of motor evoked potentials can demonstrate the involvement of cortico-spinal projections even in the absence of neuroimaging data of their damage during 48 hours.The transcranial magnetic stimulation with the analysis of motor evoked potentials is a reliable tool for diagnosing damage to cortico-spinal projections in the onset of vascular myelopathy.